Five Student Problems in Learning Arabic in Senior High School - Fitriani, Fitriani; Arifin, Zainul; Pasaleron, Roni (El-Rusyd, 2024)
Arabic language subjects must be studied, but in reality, there are still students who do not understand and master Arabic language learning because there are several problems with it. This research aims to determine the problems experienced by students in learning Arabic. This research uses qualitative methods with a case study approach. Data sources were taken from twelve informants, including school principals, teachers, and students through individual and group interviews. To strengthen the interview data, the author also made direct observations of teachers and students. All interview and observation data were analyzed using the Milles & Hubberman Interactive Analysis model. Research findings found that there were five problems students in studying Arabic in high school. The five problems are: i) lack of school facilities and infrastructure, ii) negative behavior in learning, iii) low interest in learning, iv) teachers' teaching methods are not innovative, and v) differences in students' diverse backgrounds. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.